Implementation and study of fuzzy based KY boost converter for electric vehicle charging - Jalla Upendar; Sangem Ravi Kumar; Sapavath Sreenu; Bogimi Sirisha (Institute of Advanced Engineering and Science, 2022)
Elecetric vehicle batteries require direct current (DC) current for charging; hence the circuit alternating current (AC) is converted to DC by a battery charger. Battery charger mostly consists of a rectifier and DC-DC converter with a controller built in to serve as a protective circuit. A harmonic source load is a type of electric car charger. During the AC-DC change over method, harmonic current is introduced into the power system, affecting power quality. In this study, a charging station consisting of buck boost and a charging station consisting a KY Boost converter were simulated. To maintain output voltage of DC-DC converters constant controller is used, the controller is either PI or fuzzy logic controller. So, four models are developed and simulated which are buck-boost converter controlled by proportional-integral (PI)-controller, KY-boost converter controlled by proportional integral-controller, buck boost converter controller fuzzy logic controller and KY boost-converter controlled by fuzzy logic controller. The total harmonic distortion (THD) of the four models is compared.